Risk management of emergency service vehicle crashes in the United States fire service: process, outputs, and recommendations - David P. Bui; Keshia Pollack Porter; Stephanie Griffin; Dustin D. French; Alesia M. Jung; Stephen Crothers; Jefferey L. Burgess (BMC, 2017)
Abstract Background Emergency service vehicle crashes (ESVCs) are a leading cause of death in the United States fire service. Risk management (RM) is a proactive process for identifying occupational risks and reducing hazards and unwanted events through an iterative process of scoping hazards, risk assessment, and implementing controls. We describe the process, outputs, and lessons learned from the application of a proactive RM process to reduce ESVCs in US fire departments. Methods Three fire departments representative of urban, suburban, and rural geographies, participated in a facilitated RM process delivered through focus groups and stakeholder discussion. Crash reports from department databases were reviewed to characterize the context, circumstances, hazards and risks of ESVCs. Identified risks were ranked using a risk matrix that considered risk likelihood and severity. Department-specific control measures were selected based on group consensus. Interviews, and focus groups were used to assess acceptability and utility of the RM process and perceived facilitators and barriers of implementation. Results Three to six RM meetings were conducted at each fire department. There were 7.4 crashes per 100 personnel in the urban department and 10.5 per 100 personnel in the suburban department; the rural department experienced zero crashes. All departments identified emergency response, backing, on scene struck by, driver distraction, vehicle/road visibility, and driver training as high or medium concerns. Additional high priority risks varied by department; the urban department prioritized turning and rear ending crashes; the suburban firefighters prioritized inclement weather/road environment and low visibility related crashes; and the rural volunteer fire department prioritized exiting station, vehicle failure, and inclement weather/road environment related incidents. Selected controls included new policies and standard operating procedures to reduce emergency response, cameras to enhance driver visibility while backing, and increased training frequency and enhanced training. The RM process was generally acceptable to department participants and considered useful. All departments reported that the focused and systematic analysis of crashes was particularly helpful. Implementation of controls was a commonly cited challenge. Conclusions Proactive RM of ESVCs in three US fire departments was positively received and supported the establishment of interventions tailored to each department's needs and priorities.